Students‘ Perception Towards Skkribl.io as English Media Teaching - Gymnastiar, Muhammad Rafi Abdul Jabbar (Media and Technology in Education, 2023)
Although there have been numerous studies on English media teaching in language classes, fewer studies. This qualitative case study aimed to investigate various indicators of perception, including benefits and challenges associated with Skkribl.io. Data was collected through an online questionnaire administered to learners in EFL countries. Informed consent was obtained from the participants before data collection. The collected data were analyzed using thematic analysis, involving identifying themes from learners’ responses and categorizing relevant information. The research findings were derived by summarizing and categorizing the learners’ responses based on the identified perception indicators. It was found that some challenges arose in implementing the media. But, this study also provides valuable benefits to students’ perspectives on Skkribl.io as a media for English language teaching. It is suggested that the lecturers should be prepared to adapt new teaching methods through Skkribl.io and put effort into learning new media teaching methods.